Two-fermion Composite Quasi-bosons and Deformed Oscillators - Gavrilik, A.M.; Kachurik, I.I.; Mishchenko, Yu.A. (Ukrainian Journal of Physics, 2022)
The concept of quasi-bosons or composite bosons (like mesons, excitons, etc.) has a wide range of potential physical applications. Even composed of two pure fermions, the quasi-boson creation and annihilation operators satisfy non-standard commutation relations. It is natural to try to realize the quasi-boson operators by the operators of a deformed (nonlinear) oscillator, the latter constituting a widely studied field of modern quantum physics. In this paper, it is proven that the deformed oscillators which realize quasi-boson operators in a consistent way really exist. The conditions for such realization are derived, and the uniqueness of the family of deformations under consideration is shown.